1996
DOI: 10.1007/bf00049344
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of a CCGAC cis-acting element for cold induction of the BN115 gene from winter Brassica napus

Abstract: Mutation of the core pentamer, CCGAC, of two putative low temperature responsive elements (LTREs) in the 5'-proximal region for the winter Brassica napus cold-induced gene BN115 was carried out. Analyses of transient expression of the resultant mutated BN115 promoter-GUS fusions revealed the loss of low-temperature regulation by the promoter. This indicates that the CCGAC sequence is critical to the low-temperature response in the BN115 gene. In contrast, mutation of two G-boxes, CACGTG, staggered between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
158
1
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(165 citation statements)
references
References 14 publications
3
158
1
1
Order By: Relevance
“…Among genes up-regulated by 30 min of EL, we found a number of known light-regulatory elements, including the Gbox (CACGTG) (24), and a GCCAC motif previously identified as overrepresented in light-induced promoters (SORLIPs) (25). We also found an ACGT motif (26), a CCGAC motif (27), and an ATCCAAT motif (28) (Fig. S1F).…”
Section: El Triggers Redox Stress and Changes The Expression Of Hundrmentioning
confidence: 74%
“…Among genes up-regulated by 30 min of EL, we found a number of known light-regulatory elements, including the Gbox (CACGTG) (24), and a GCCAC motif previously identified as overrepresented in light-induced promoters (SORLIPs) (25). We also found an ACGT motif (26), a CCGAC motif (27), and an ATCCAAT motif (28) (Fig. S1F).…”
Section: El Triggers Redox Stress and Changes The Expression Of Hundrmentioning
confidence: 74%
“…Analysis of the AtDGK2 promoter for the presence of potential cis regulatory elements using the PLACE (available on the World Wide Web at www.dna.affrc.go.jp/htdocs/PLACE/ fasta.html) and PlantCARE (available on the World Wide Web at intra.psb.ugent.be:8080/PlantCARE) interfaces revealed cis elements that may contribute to cold-responsive gene expression (Fig. 9a) (43)(44)(45)(46). We tested the transcriptional activation of AtDGK2 by subjecting promAtDGK2::GUS reporter lines to cold stress.…”
Section: Fig 2 Phylogenetic Analysis Of Plant Dgk Isozymesmentioning
confidence: 99%
“…An important advance in this regard was the recent identification of the C-repeat͞dehydration responsive element (DRE) cis-acting DNA regulatory element (6)(7)(8). The element, which has a 5-bp core sequence of CCGAC, designated the C-repeat (7), is present in one to multiple copies in the promoters of many cold-regulated plant genes, including the Arabidopsis genes COR15a (7) and COR78͞RD29A (ref.…”
mentioning
confidence: 99%
“…The element, which has a 5-bp core sequence of CCGAC, designated the C-repeat (7), is present in one to multiple copies in the promoters of many cold-regulated plant genes, including the Arabidopsis genes COR15a (7) and COR78͞RD29A (ref. 6; COR78 and RD29A are alternative designations for the same gene) and the Brassica napus gene BN115 (8). Deletion analysis of the Arabidopsis COR15a promoter indicated that the C-repeat might be part of a cis-acting cold-regulatory DNA element (7).…”
mentioning
confidence: 99%